Gaya Kepemimpinan Kepala Madrasah dan Implikasinya terhadap Kedisiplinan Tenaga Kependidikan di Madrasah Aliyah Laboratorium Jambi - Rahmatang Rahmatang; Samsu Samsu; Ahmad Ansori (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to analyze the implementation of the principal’s leadership styles in improving the discipline of educational staff at Madrasah Aliyah Laboratory Jambi. This research employed a qualitative descriptive approach. Data were collected through observations, in-depth interviews, questionnaires, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the principal applied a situational leadership approach by combining democratic, laissez-faire, and authoritarian leadership styles. Among these, democratic leadership was the most dominant and effective in enhancing staff discipline. The main challenges included commuting distance, welfare issues, kinship relationships, and individual character differences. To address these challenges, the principal implemented a reward and punishment system. This study concludes that adaptive and contextual leadership plays a crucial role in improving the discipline of educational staff in Islamic secondary education institutions.